Chemohyperthermia in non-muscle-invasive bladder cancer: An overview of the literature and recommendations. (18th May 2016) - Liem, Esmee I.M.L.; Crezee, Hans; de la Rosette, Jean J.; de Reijke, Theo M.
Abstract: Non-muscle-invasive bladder cancer (NMIBC) is characterised by a high risk of recurrence for the present standard treatment of transurethral resection of the bladder (TURB) followed by intravesical instillation of Mitomycin-C (MMC) or bacillus Calmette–Guérin (BCG). To decrease this high recurrence rate, alternative treatments are studied. Intravesical MMC combined with hyperthermia could be an interesting alternative active treatment for intermediate- and high-risk NMIBC, and has been investigated in the past years. Hyperthermia, raising tumour temperatures to 40–44 °C, can be achieved with several hyperthermia systems, based on three different techniques: 1) intravesical microwave induced heating, 2) conductive heating, and 3) loco-regional, using external radiofrequency antennas. In this review an overview is given of the available hyperthermia systems and the reported outcomes. Future directions are discussed. Optimal implementation of a combined regimen of MMC and hyperthermia requires further clinical trials to identify patients who will benefit most from this treatment, to optimise treatment schedules and to compare the efficacy of different hyperthermia devices.